THE FUNCTION OF LEGAL REASONITY IN COURT JUDGEMENT (MODEL ON FINDING THE LAW REFLECTY PANCASILA VALUE) - Deka Rachman Budihanto (Yuridika, 2017)
Legal research is a process to determine the rule of law, principles of law and legal doctrines in order to address the legal issues at hand. This study using a type of normative juridical (legal research). Rechtvinding understanding in Indonesian as legal discovery (translated literally) could mislead rechtvinding function is to find concrete norm to associate the relevant legal facts. Adhering to the understanding of the rechtvinding the judge in carrying out its functions prosecute a legal case can not be separated from efforts to find concrete norms to be linked to the fact the law. Furthermore, when the facts of law has no grounding norms that govern mutatis mutandis thus not regulated in the rules of positive law and customary law. Scholasticism and dialectic method is used as a support hermeneutic interpretation of legal facts to me recht construction of a new legal norm normative ideas should not be separated from Idee recht itself. Rechvinding model contained in the provisions of the Basic Law of Judicial Authority Article 1 in Conjunction with Article 5, Article 10 in conjunction with Article 50 1 for the model Rechtvinding is the approach taken by norma series is a concept of morals and justice and practices considered society as law and the criminal law model rechtvinding is also banned norma concrete (new), to assess the actions (act) so that an exit permit from the actions that have not been regulated in the act so that such actions are not punished.